2021
DOI: 10.1051/e3sconf/202127310034
|View full text |Cite
|
Sign up to set email alerts
|

The concept of success in representing codependent women: transformation in the conditions of the COVID-19 pandemic threat

Abstract: The presence of codependent behavior affects many areas of life, while distorting most of the personality's beliefs. Some of the most striking distortions concern the notion of success. At the same time, in conditions of uncertainty (for example, during the COVID-19 pandemic), these changes began to be of a special nature, which can be reflected not only in the features of psychocorrectional measures, but also on the quality of life of the codependent individual as a whole. The empirical object of the study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…ere is also evidence of a lack of psychological boundaries and a tendency to violate those of others, negative attitudes towards oneself and others, and a lack of personal resources (Khazova & Varioshkina, 2022). Additionally, codependent individuals tend to ignore their own needs (Kolenova, 2019;Moskalenko, 1994), experience auto-and heterogeneous anger, and exhibit negative generalization of selfrelationship, among other things (Tascheva & Bedredinova, 2016). Rogozina (2020) has shown that the degree of marital codependency is closely related to the structure of the self-relationship, and it can be assumed that the considered components of the self-relationship play a signi cant role in the formation and degree of marital codependency in women.…”
Section: Self-attitude Studies In Codependent Individualsmentioning
confidence: 99%
“…ere is also evidence of a lack of psychological boundaries and a tendency to violate those of others, negative attitudes towards oneself and others, and a lack of personal resources (Khazova & Varioshkina, 2022). Additionally, codependent individuals tend to ignore their own needs (Kolenova, 2019;Moskalenko, 1994), experience auto-and heterogeneous anger, and exhibit negative generalization of selfrelationship, among other things (Tascheva & Bedredinova, 2016). Rogozina (2020) has shown that the degree of marital codependency is closely related to the structure of the self-relationship, and it can be assumed that the considered components of the self-relationship play a signi cant role in the formation and degree of marital codependency in women.…”
Section: Self-attitude Studies In Codependent Individualsmentioning
confidence: 99%